2013
DOI: 10.1002/erv.2226
|View full text |Cite
|
Sign up to set email alerts
|

Punishment and Reward Sensitivity: Are Naturally Occurring Clusters in These Traits Related to Eating and Weight Problems in Adolescents?

Abstract: Little is known about the role of sensitivity to punishment (SP) and reward (SR) in eating problems during adolescence. Therefore, the aim of the present study was to examine the naturally occurring clusters of high and low SP and SR among nonclinical adolescents and the between-cluster differences in various eating problems and weight. A total of 579 adolescents (14-19 years, 39.8% boys) completed the Sensitivity to Punishment and Sensitivity to Reward Questionnaire (SPSRQ), the Behavioural Inhibition System … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
51
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(60 citation statements)
references
References 73 publications
8
51
1
Order By: Relevance
“…In turn, AgRp-containing neurons in the arcuate nucleus mainly target neurons in the paraventricular nucleus that express melanocortin 4 receptors (MCR4; . Stimulation of the MCR4 decreases food intake (Adan and Kas, 2003;Lubrano-Berthelier et al, 2003;Srinivasan et al, 2004;Kim et al, 2008).…”
Section: Critical Brain Areas Of the Cns Control Food Intake: Autonommentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, AgRp-containing neurons in the arcuate nucleus mainly target neurons in the paraventricular nucleus that express melanocortin 4 receptors (MCR4; . Stimulation of the MCR4 decreases food intake (Adan and Kas, 2003;Lubrano-Berthelier et al, 2003;Srinivasan et al, 2004;Kim et al, 2008).…”
Section: Critical Brain Areas Of the Cns Control Food Intake: Autonommentioning
confidence: 99%
“…A working hypothesis: decision making to eat could partly depend on neural pathways concerned with dealing with stress. A, Efferent neurons of the mPFC mainly target the DR (Sesack et al, 1989;Peyron et al, 1998;Vertes, 2004) and contain glutamate (GLU) (Lee et al, 2003). With regard to the reciprocal descending projections, 5-HT neurons in the mPFC mainly arise from the DR and send axon collaterals to the NAc (Van Bockstaele et al, 1993).…”
Section: Critical Brain Areas Of the Cns Control Food Intake: Autonommentioning
confidence: 99%
See 1 more Smart Citation
“…Studies showed that individuals higher in SR have a greater risk of being overweight, experience more food cravings and episodes of emotional eating and have a higher activation of brain areas implicated in food reward [14,20,21,[28][29][30]. The few studies that addressed SR in adolescence concentrated mainly on dysfunctional eating [31,32]. This scarcity is unfortunate as SR increases from childhood to adulthood with a peak in adolescence, while at the same time inhibitory control matures at a slower pace [33].…”
Section: Introductionmentioning
confidence: 99%
“…Reward sensitivity is also associated with increased vulnerability to disorders characterized by poor impulse control, such as Attention Deficit and Hyperactivity Disorder (ADHD, Mitchell and Nelson-Gray, 2006), substance use, dependence or addiction (Knyazev, 2004;Pardo et al, 2007;Yen et al, 2012), eating disorders (Glashouwer et al, 2014;Matton et al, 2014Matton et al, , 2013, and cluster B personality disorders (Bijttebier et al, 2009;Pastor et al, 2007;Taylor et al, 2006). Patients with these disorders also tend to show impairments in response inhibition tasks, especially in ADHD, where deficient behavioral inhibition has been considered a core feature of the disorder (Alderson et al, 2007).…”
Section: Introductionmentioning
confidence: 99%